Malignant perivascular epitheloid cell tumour (PEComa) of the lung – a rare entity - Chakrabarti Amitabha; Bandyopadhyay Manujesh; Purkayastha Biswarup (Innovative Surgical Sciences, 2017)
Malignant Perivascular Epitheloid Cell Tumour (PEComa) of the lung is very rare, with only six cases reported in literature. This case presented with a large mass originating from right upper lobe of the lung with dilemma in its histopathological diagnosis and management. Postoperative histopathology after a right upper and middle lobectomy describes a tumour with an alveolar/nested pattern of growth and epitheloid morphology with expression of TFE-3 and diagnosed as PEComa. After 6 months the patient had a local recurrence inside the thorax & chest wall.This case qualifies it as a rare type of malignant PEComa with younger age of presentation, aggressive clinical behaviour & malignant histological features along with TFE3 positivity on immunohistochemistry. This case is probably the first of its kind with the largest reported size involving two lobes of the lung.